Solidarity; syncretism of peace and friendship - Seyed Mohsen Alavipour; Morteza Bahrani (حقوق بشر, 2009)
Considered as a fundamental virtue in the classical political thought, “friendship” even outshined the other important virtues like “justice”. However, the emergence of modernity and the consequent epistemological rupture caused to the prevalence of other concepts as “security” and “peace” over “friendship”. Thus, humans, as the wolves of each other, forgot about classical virtues including “friendship”. However, the contemporary criticism of modern thought shows the necessity of revival and reinterpretation of classical political concepts. Meanwhile, returning to the importance of “friendship” in the classical thought, Jürgen Habermas syncretizes “friendship” and “peace”, believing that with making “solidarity” central, those two concepts can be realized simultaneously in the society. Thus, “solidarity” is the source of legitimate norm establishing in the modern society. yle='font-size: 11.0pt;letter-spacing:-.2pt'>Plato’s opposition to democracy –indeed only to a certain kind of it– shows that there is no necessary correlation between justice and peace on the one hand and democracy on the other hand.